Linhas e entrelinhas do ensino emergencial: um olhar para a disciplina de língua portuguesa - Viana, Cristiane Alves (2023)
During the 2020-2021 biennium, the Covid-19 pandemic caused the longest closure of schools ever recorded in the history of the state of Parana, a period in which the spaces, resources and activities of students and teachers had to be reformulated to meet to the need for social isolation, resulting in the implementation of emergency teaching. Faced with this unprecedented scenario, the relevance of this research lies mainly in the need to carry out a historical record of this period. As a general objective, we sought to investigate the developments of emergency teaching and its possible implications in the learning of the Portuguese language by students in the 3rd year of High School in state public schools in the municipality of Santa Terezinha de Itaipu. As specific objectives we list: I) Historically contextualize emergency teaching in the state public teaching network of Parana; II) Analyze how the Secretary for Education and Sport (SEED) reorganized the teaching – learning process in the 2020-2021 biennium, focusing on the subject of Portuguese Language in High School. III) Understand how students and teachers of the Portuguese Language of the 3rd grade of High School in public schools in the state of Santa Terezinha de Itaipu experienced the period of emergency teaching. IV) To identify how Portuguese Language students and teachers in the 3rd year of High School at public schools in the state public school network in the municipality of Santa Terezinha de Itaipu evaluate the learning developed during the period of emergency teaching. The questions that drove the research are: did the way in which emergency teaching was organized by SEED meet the reality and needs of students, teachers and schools? Did this organization allow for effective learning by students in the Portuguese Language discipline? In order to meet the research objectives and seek answers to these questions, an analysis of the documents that guided the organization of emergency teaching in the state public education network of Parana, was carried out and a survey was carried out in the four schools belonging to the referred network located in the municipality of Santa Terezinha de Itaipu, using the semi-structured interview with the Portuguese Language teachers and the online questionnaire with the students as data generation instruments. The data generated through these instruments were analyzed and interpreted through the Discursive Textual Analysis method and the discussions were anchored in the assumptions of historical-critical pedagogy. The study is of a basic nature, exploratory – descriptive, with articulation between qualitative and quantitative approaches. The results indicate that all the reorganization carried out with emergency teaching did not prevent the suspension of face-toface classes from having negative impacts on student learning, however the insertion of digital technologies with this teaching format brought new possibilities to conducting the teaching-learning process. The expectation of students and teachers, with the return to face-toface classes, is to focus on resuming contente in order to overcome or at least mitigate the learning gap resulting from the pandemic.